RIRS in the elderly: Is it feasible and safe?. (June 2017) - Berardinelli, F.; De Francesco, P.; Marchioni, M.; Cera, N.; Proietti, S.; Hennessey, D.; Dalpiaz, O.; Cracco, C.; Scoffone, C.; Giusti, G.; Cindolo, L.; Schips, L.
Abstract: Background: The aim of this study was to compare the safety and efficacy of RIRS in men ≥65 years to those <65 years. Materials and methods: Patients who underwent RIRS were prospectively collected from March 2013 to March 2014 in 5 European centers. Perioperative outcomes and complications in elderly men were compared with men <65 years. Univariable and multivariable analyses were performed for factors predicting overall complications. The groups were compared using Mann–Whitney U test. Categorical variables were compared using chi-squared test and the Yates correction or the Fisher's exact test. Results: A total of 399 patients with renal stones were included, 308 (77.19%) were aged <65 years, 91 (22.8%) were aged ≥65 years. Elderly patients were more likely to have higher ASA scores (35.7% vs 92.3%; p < 001), Charlson Comorbidity Index (1.8 vs. 5.2, p < 0.001), hyperlipidemia (10.06% vs. 30.76%; p = 0, 0005) and coronary heart disease (5.51% vs. 17.58; p = 0.005) compared to younger cohort. Perioperative outcomes (stone free rate, operative time and re-intervention rate) did not show differences between the two groups (p > 0.05). Surgical and medical complication rates were similar between the cohorts (14.28% vs 9.89%; p = 0.38). Multivariate analysis did not identify any predictive factors of complications among the two groups (p > 0.05). Conclusions: In this study, elderly RIRS patients had comparable short term efficacy and perioperative complications to younger patients, despite a higher prevalence of comorbidity. Age itself should not be considered as a risk factor for the development of complications in patients undergoing RIRS for renal stone. Highlights: RIRS has gain more acceptance as first line therapy in renal stones up to 2 cm. RIRS is an effective and safe technique regardless the age of patients. RIRS is a surgical technique with a low complication rate.